Knowledge, Attitude and Practice of Parents of Children with Childhood Asthma in a Tertiary Care Hospital - Aziz, Afrin; Shamsad, Iffat Ara; Sharmin, Tasnuva; Hussain, Sharmin; Ara, Effat; Nahar, Nurun; Hoque, Md Obidul (Journal of Dhaka Medical College, 2024)
Back ground: Asthma is one of the most common reasons that children visit doctors, miss days at school or are admitted to hospital. If asthma is well managed, child should be able to lead a healthy and active life. Methods: The study aims to investigate parental knowledge, attitudes about childhood asthma, and practices regarding the management of their children’s asthma. An observational cross-sectional study was conducted among parents of children aged between 2 and 12 years with asthma who had visited the outpatient or inpatient department of Pediatrics at Dhaka Medical College Hospital over a period of approximately 6 months. Data were collected using a preformed Knowledge, Attitude, and Practice (KAP) questionnaire. Results: Total 110 parents of children with childhood asthma were interviewed in this study. There were 63 (57.3%) male and 47 (42.7%) female with M:F ratio 1.34:1 (Slightly male predominance). Most of the patients 57(87.6%) visited in out-patient department (OPD). Almost half of the parents (52.7%) knew their children had asthma. Most of the parents (80.9%) thought oral form of drug (syrup/ tablet) is better than inhaler. Almost two-third parents believed asthma can be cured and they did not know the importance of adherence with asthma medications. The overall parental knowledge was poor (49.09%). Nearly half of them (49.09%) had negative attitude about childhood asthma & 50.9% parents had poor practice about avoidance of allergens, use of asthma medications and regular follow up of their children. Knowledge, attitude and practice are significantly associated with education, socioeconomic condition and living area. Statistically significant positive correlation has been found between knowledge and practice, but knowledge and attitude has not showed significant positive correlation. J Dhaka Med Coll. 2022; 31(2) : 194-200